China in the twenty-first century: Politics, economy, and society - ITOH, Hiroshi (United Nations, 1997)
China has experienced tremendous change during the People's Republic, particularly over the past 15 years, when it has begun a shift from a centrally planned economy to a market-oriented system. This book, based on an international symposium held at Aoyama Gakuin University, Tokyo, attempts to picture the landscape of China in the twenty-first century. The book opens with essays by Rong Yiren, vice-president of the People's Republic of China, and Helmut Schmidt, former chancellor of Germany. The second part considers the Chinese economy, management, politics, and society in the twenty-first century. The final section presents a panel discussion in which eight of the contributors debate the political strategies of the revolution and liberalization that have wrought so rapid a change in China's economy and society.